Influence of Entrepreneurial Characteristics on the Performance of Small and Medium Food Enterprises in Valikamam area of the Jaffna District - Sarujan, S.; Sooriyakumar, K. (University of Jaffna, 2015)
This paper examines the relationship between entrepreneurial characteristics and the performance of the small and medium food enterprise in the Valikamam area of the Jaffna district. Employment growth and the average monthly profit of the enterprises were used as indicators for the performance of these enterprises. Of the total of 180 small and medium food enterprises in the Valikamam area, Sixty three enterprises were randomly selected for this study. Firm characteristics and other variables are used as control variables in this analysis. Two linear regression models for the rate of employment growth and the average monthly profit of the enterprises were developed, using Ordinary Least square method. The results indicate that the firm characteristics such as age of the firm, initial numbers of employees and initial investment has a significant effect on the employment growth and entrepreneurial characteristics such as age and experience of entrepreneur have significant effect on the profit of enterprises. One of the important findings of this study is that one percent increase in experience causes 12% increases in profit when an entrepreneur is 30 years old. Experience shows a negative relationship with the profit when an entrepreneur is above 40 years old. This suggests that young entrepreneurs have gained better technology on production and business management through their work experience than older entrepreneurs. Therefore, training programs and workshops on production technology and business management for the entrepreneurs will significantly enhance the profit of the small and medium enterprise in this region
Keywords: Small Medium Enterprises; Entrepreneurial characteristics; Employment growth; Profit; Ordinary Least Square method